2019
DOI: 10.1111/joa.13058
|View full text |Cite
|
Sign up to set email alerts
|

Myoarchitectural disarray of hypertrophic cardiomyopathy begins pre‐birth

Abstract: Myoarchitectural disarray – the multiscalar disorganisation of myocytes, is a recognised histopathological hallmark of adult human hypertrophic cardiomyopathy (HCM). It occurs before the establishment of left ventricular hypertrophy (LVH) but its early origins and evolution around the time of birth are unknown. Our aim is to investigate whether myoarchitectural abnormalities in HCM are present in the fetal heart. We used wild‐type, heterozygous and homozygous hearts (n = 56) from a Mybpc3‐targeted knock‐out HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 52 publications
(111 reference statements)
2
65
0
Order By: Relevance
“…The heart ultrastructural organization is needed for efficient heart pumping and is linked to the cell metabolism 2325 . Structural malformations in the chambers, valves or vessels of the heart, together with disruptions to the organization or number of cardiac cells, and/or their ultrastructure, can compromise the heart’s ability to pump blood efficiently 8,10,13,26,27 . Anomalous structural and ultrastructural architectures can be detrimental to the heart’s capacity to adapt to new conditions imposed by corrective surgeries or other therapies intended to repair structural congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The heart ultrastructural organization is needed for efficient heart pumping and is linked to the cell metabolism 2325 . Structural malformations in the chambers, valves or vessels of the heart, together with disruptions to the organization or number of cardiac cells, and/or their ultrastructure, can compromise the heart’s ability to pump blood efficiently 8,10,13,26,27 . Anomalous structural and ultrastructural architectures can be detrimental to the heart’s capacity to adapt to new conditions imposed by corrective surgeries or other therapies intended to repair structural congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…While the structural (morphological or “geometrical”) characteristics of heart malformations have been extensively studied, it is largely unknown whether cardiac cells from malformed hearts are normal or to what extent they are compromised. Recent studies reveal an abnormal orientation of myocardial cells (the heart muscle cells) within CHD hearts 810 . Myocardial cells are elongated, cylindrical-like cells, that contract along their long axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMDD independent stand-alone studies researching genetic regulation of mouse development include the analysis of: normal and abnormal cardiovascular development [49][50][51][52][53][54][55][56][57][58][59][60][61]; the development of the limbs, cloaca and pancreas [42,[62][63][64]; ciliopathies [65]; and the characterisation of cardiac defects in Down syndrome mouse models [66,67]. Despite its value for analysing such processes in embryos between embryonic day E8.5 and E14.5, when organogenesis is already finished, HREM also proved its value for analysing developmental processes in very early embryos immediately after implantation [68].…”
Section: Mouse Embryosmentioning
confidence: 99%
“…However, the mechanisms that lead to an anomalous cardiac architecture in CHD and the clinical consequences of it are unknown. Recent studies have revealed an abnormal orientation of myocardial cells (the heart muscle cells) within CHD hearts ( Garcia-Canadilla et al, 2019 ; Stephenson et al, 2018 ; Garcia-Canadilla et al, 2018 ). Myocardial cells are elongated, cylindrical-like cells, that contract along their long axis.…”
Section: Introductionmentioning
confidence: 99%